'Habitually deciding' or 'habitually doing'? A response to Hagger (2019). (March 2020) - Gardner, Benjamin; Rebar, Amanda L.; Lally, Phillippa
Abstract: Hagger (2019) offers an insightful synthesis of recent theoretical and empirical developments in understanding of habit and its relevance to physical activity. This commentary extends coverage of one such advance, namely the distinction between two manifestations of habit in physical activity: habitually 'deciding' to engage in activity (i.e. habitual instigation), and habitually 'doing' the activity (habitual execution). We explore the rationale for this distinction and argue that most contemporary theory and evidence around habitual physical activity – and by extension, Hagger's review – implicitly focuses on instigation and neglects execution. We offer hypotheses around the potential roles that habitual execution may play in physical activity. Broadening the scope of inquiry within the field to more fully encompass habitual performance would achieve a more comprehensive and informative account that incorporates concepts of skill acquisition and mastery.